2020
DOI: 10.1016/j.seizure.2020.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the ketogenic diet in patients with Dravet syndrome: A meta-analysis

Abstract: Dravet syndrome is an infantile epilepsy syndrome with drug resistant seizures and cognitive impairment. The aim of this meta-analysis was to summarize the findings of relevant published studies to identify the efficacy of a ketogenic diet in patients with Dravet syndrome and their compliance thereof, and to provide useful information for clinical practice. Methods: The PubMed, Embase, Wanfang, and CNKI databases were searched for relevant studies published up to September 25, 2019; the included studies were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 37 publications
0
12
0
2
Order By: Relevance
“…A meta-analyis examining the efficacy of ketogenic diet in DS by Wang YQ et al displayed a combined efficacy rate for ≥50 % seizure reduction was 63 % at 3, 6 and 12 month checkpoints in 167 combined DS children [55]. Another study of 20 children also reported ≥50 % seizure reduction in 80 % of them [56].…”
Section: Treatmentmentioning
confidence: 99%
“…A meta-analyis examining the efficacy of ketogenic diet in DS by Wang YQ et al displayed a combined efficacy rate for ≥50 % seizure reduction was 63 % at 3, 6 and 12 month checkpoints in 167 combined DS children [55]. Another study of 20 children also reported ≥50 % seizure reduction in 80 % of them [56].…”
Section: Treatmentmentioning
confidence: 99%
“…Although KD is an established first‐line therapeutic concept for GLUT1 deficiency syndrome, the list of possible indications comprises different genetic epilepsy syndromes including the Dravet syndrome, which is characterized by a severe clinical phenotype and a poor pharmacoresponsiveness 12 . For Dravet syndrome a recent meta‐analysis has suggested an improvement of seizure control and behavioral symptoms in response to the KD 13 . This finding supports the recommendation of KD for Dravet patients with failure to respond to three or four different antiseizure drugs 14 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to epilepsy control, cognitive function improved in 22 patients, language progression in 14 patients, and motor function improved in 13 patients ( 69 ). A recent meta-analysis also concluded that 63, 60, and 47% of DS patients had a ≥50% reduction in seizures at 3, 6, and 12 months after KD, and the seizure control rates at 6 and 12 months were 78 and 49%, respectively ( 37 ). The KD not only effectively controlled seizures, but also improved cognitive, motor and other behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…The KD not only effectively controlled seizures, but also improved cognitive, motor and other behaviors. Even in patients with unreduced seizures, the quality of life was improved, and the number of AEDs reduced to one or two on the ketogenic diet ( 37 , 42 ). Caraballo et al ( 42 ) believed that KD treatment should be considered immediately after three failed AEDs.…”
Section: Discussionmentioning
confidence: 99%